Strong Replication Interference Between Hepatitis Delta Viruses in Human Liver Chimeric Mice - Giersch, Katja; Hermanussen, Lennart; Volz, Tassilo; Volmari, Annika; Allweiss, Lena; Sureau, Camille; Casey, John; Huang, Jiabin; Fischer, Nicole; Lütgehetmann, Marc; Dandri, Maura (Frontiers in Microbiology, 2021)
Background: Hepatitis D Virus (HDV) is classified into eight genotypes with distinct clinical outcomes. Despite the maintenance of highly conserved functional motifs, it is unknown whether sequence divergence between genotypes, such as HDV-1 and HDV-3, or viral interference mechanisms may affect co-infection in the same host and cell, thus hindering the development of HDV inter-genotypic recombinants. We aimed to investigate virological differences of HDV-1 and HDV-3 and assessed their capacity to infect and replicate within the same liver and human hepatocyte in vivo. Methods: Human liver chimeric mice were infected with hepatitis B virus (HBV) and with one of the two HDV genotypes or with HDV-1 and HDV-3 simultaneously. In a second set of experiments, HBV-infected mice were first infected with HDV-1 and after 9 weeks with HDV-3, or vice versa. Also two distinct HDV-1 strains were used to infected mice simultaneously and sequentially. Virological parameters were determined by strain-specific qRT-PCR, RNA in situ hybridization and immunofluorescence staining. Results: HBV/HDV co-infection studies indicated faster spreading kinetics and higher intrahepatic levels of HDV-3 compared to HDV-1. In mice that simultaneously received both HDV strains, HDV-3 became the dominant genotype. Interestingly, antigenomic HDV-1 and HDV-3 RNA were detected within the same liver but hardly within the same cell. Surprisingly, sequential super-infection experiments revealed a clear dominance of the HDV strain that was inoculated first, indicating that HDV-infected cells may acquire resistance to super-infection. Conclusion: Infection with two largely divergent HDV genotypes could be established in the same liver, but rarely within the same hepatocyte. Sequential super-infection with distinct HDV genotypes and even with two HDV-1 isolates was strongly impaired, suggesting that virus interference mechanisms hamper productive replication in the same cell and hence recombination events even in a system lacking adaptive immune responses.